(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: The rapid growth of financial technology (Fintech) has transformed banking services globally, including in Nepal. Nepalese banks are increasingly offering Fintech services, but adoption and acceptance among users remain uneven due to technological, infrastructural, and knowledge-related challenges. Understanding the factors that influence user acceptance is crucial for maximizing the potential of Fintech in the Nepalese banking sector. Purpose: This study aims to identify and analyze the key factors affecting the acceptance of Fintech services offered by Nepalese banks, with a focus on user perceptions, attitudes, and behavioral intentions in Kathmandu Valley. Design/methodology/approach: An explanatory research design guided by the Technology Acceptance Model (TAM) was employed. Data were collected from respondents using a self-administered questionnaire via Kobo Toolbox, and convenience sampling was applied. The study analyzed both descriptive and inferential data using Smart PLS 4.0 to test relationships among perceived usefulness, perceived ease of use, security, attitude, and behavioral intention to use Fintech services. Findings: The results show that most respondents are aware of and knowledgeable about Fintech services provided by Nepalese banks. The typical users are unmarried youth, predominantly women, working in private sector roles. Lack of infrastructure and limited knowledge about Fintech emerged as the primary challenges to adoption. Key solutions identified include providing adequate training, improving user-friendly interfaces, and enhancing Fintech services accessibility. Perceived usefulness and perceived ease of use significantly influence users’ attitudes toward Fintech services, while security was found to have an insignificant effect. Attitude acts as a mediator between perceived usefulness, ease of use, and behavioral intention to adopt Fintech. Conclusion: The study concludes that user perceptions of usefulness and ease of use are critical drivers of Fintech adoption in Nepalese banks. Addressing infrastructural gaps, improving service usability, and educating users can significantly enhance acceptance and adoption rates. These insights are valuable for banks, policymakers, researchers, and other stakeholders aiming to promote Fintech adoption in emerging markets like Nepal. Keywords: Fintech, TAM, Adoption/Acceptance, SEM, Bank